2017
DOI: 10.1186/s12936-017-2095-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the use of malaria prevention strategies by women in Senegal: a cross-sectional study

Abstract: BackgroundThe World Health Organization (WHO) recommends the use of insecticide-treated nets (ITNs) and intermittent preventive treatment in pregnancy (IPTp) as a cost-effective intervention for the prevention of malaria during pregnancy in endemic areas. This study was conducted to investigate: (1) the extent of use of both IPTp and ITNs, and (2) conduct multinomial regression to identify factors affecting the optimal usage of IPTp and ITNs among women with a recent pregnancy in Senegal.MethodsData was drawn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
29
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 23 publications
10
29
3
Order By: Relevance
“…This supports previous findings that ITN utilization is more prevalent in rural Nigeria compared to the urban settings [38]. However, most previous studies have reported contrary finding from Nigeria [39] and other SSA countries, such as Ghana [36], Equitorial Guinea [40], Senegal [41] and Ethiopia [33]. Even where more rural have possessed ITNs in Nigeria, utilization has been reported to be low [29,42].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This supports previous findings that ITN utilization is more prevalent in rural Nigeria compared to the urban settings [38]. However, most previous studies have reported contrary finding from Nigeria [39] and other SSA countries, such as Ghana [36], Equitorial Guinea [40], Senegal [41] and Ethiopia [33]. Even where more rural have possessed ITNs in Nigeria, utilization has been reported to be low [29,42].…”
Section: Discussionsupporting
confidence: 85%
“…The finding is also consistent with evidence from the 2010 and 2015 Nigeria Survey reports [14,15] and national malaria operational plan [45]. Although countless advantageous factors enable urban residents to possess and utilize ITN [39,41], this finding is plausible as most previous ITN initiatives have targeted rural residents as a way of bridging this gap [27,46]. Rural based campaigns have also taken place such as the one that occurred in the Enugu State [47].…”
Section: Discussionsupporting
confidence: 84%
“…This result is similar to that reported in the most recent Ghana Demographic and Health Survey in which the coverage of the recommended three or more doses of IPTp-SP was 50.6% and 36.6% among women in the highest wealth quintile and those in the lowest quintile, respectively 37. Also, similar results have been reported in Senegal,38 where women in richer or middle wealth quintile were more likely to use the recommended doses of IPTp.…”
Section: Discussionsupporting
confidence: 84%
“…In the current study therefore, only 37% of the mothers were able to make the required eight ANC visits. This also affected the number of SP doses received [17], as early ANC visit enables the uptake of more doses of SP [21, 22]. Even though most of the women received the WHO recommended number of SP doses of three or more, which was the requirement of the old Ghana malaria control programme policy, only 16% of them received the five doses recommended by the new Ghana policy.…”
Section: Discussionmentioning
confidence: 99%